Homonym Vocabulary in Arabic - Suhada, Oman Karya; Pritantoro, Wendy Morrizha; Huda, Miftachul (The Progress: Journal of Language and Ethnicity, 2022)
Sometimes the expression of a word has two meanings because it is called in different places, in linguistic studies it is called a homonym and in balaghah science, it is called Jinas. The purpose of this study is to find out homonym vocabulary in Arabic, especially in the form of isim jamid. This study uses a descriptive method with a content analysis model. The data source is several Arabic vocabulary from the dictionary "mu'jam siyaqi li al-kalimat al-asya'iyyah by Dr. Mahmud Ismail Sinni and "Mu'jam al-Lughah al-Arabiyah al-Muaashiroh" by Dr. Ahmad Mukhtar Umar. The conclusion of this study is that there are several homonymous vocabularies in Arabic with the form of isim jamid, including: إِبْرَةٌ (Needle, Bring into conflict); أَدَبٌ (Morals, Literature); بكرة (Morning, Tomorrow); بَيْتٌ (Home, Verse); جَبْهَةٌ (Forehead, Community, batlefield); جُحْرٌ (Hole, Unhealthy Palce); جَدْوَلٌ (River, Schedule); جَدٌّ (Granpa, Luck, Wealth, Majesty); جَرِيْدَةٌ (Newspaper, Cavalry, Midrib); جُزْءٌ (Some of, Juz, Fate); جُمْلَةٌ (Sentence, All); جَوٌّ (Weather, Air); حجة (Argument, Expert, Enmity); خَاتِمٌ (Ring, Stamp, Last); خَالٌ (Uncle, Mole, Cloud, Arogant); خُرْطُوْم (Khartoum, Trunk, Wine), دَقِيْقٌ (Wheat flour, Deep understanding, Short guy); رِبَاطٌ (Relationship, Promise, Shoelaces, rope, Ribath); زُبْدَةٌ (Butter, Basic); سَاعَةٌ (For a moment, One hour, Doomsday); سَبْعُ (Wild animal, Seven); سُلَالَةٌ (Sperm, Lineage); سِنٌّ (Teeth, Age); عَيْنٌ (Eye, Spy, Spring); كأس (Glass, Trophy, Wine); هِلَال (crescent moon, Lunula, Brecket).